Recent findings on corrosion of ferritic stainless steel weldments: A review - Ndukwe Agha Inya; Dan Nsikan Etim; Anaele Justus Uchenna; Agu Paulinus Chukwudi (Zaštita Materijala)
This study covers the review of the degradation of ferritic stainless-steel weldments between 2015 and 2022. The industrial and automotive sectors make extensive use of ferritic stainless steel (FSS) due to its superior oxidation and corrosion resistance, low price, high thermal conductivity, and low thermal expansion. However, it has been reported that ferritic stainless steel is harder to weld than austenitic stainless steel and that doing so would probably result in a weaker welded joint owing to the coarsening of grains high welding temperatures. According to past research, the amount of heat applied during the welding procedure affected how soon the FSS (409 M) weldment degraded after being exposed to NaCl (3.5%) medium. The coarsening of the grains was considered to be the cause of this. When the shielding gas' CO2 content increased, the intergranular corrosion of the FSS weld metal was found to increase. Welds made with the ER430LNb filler metal had significantly lower intergranular corrosion of FSS (AISI 441) than those made with the ER430Ti filler metal. It was discovered that boiling Cu-CuSO4 - 50% H2SO4 solution increased the corrosion rate for the FSS (AISI 430) weldment more than boiling 40% HNO3 Solution. Weldments made of FSS (AISI 430) were found to be negatively affected by the CuCuSO4 - 50% H2SO4 environment in terms of intergranular corrosion attack.